Effects of organic matter additions on the soil microbial population and associated stoichiometry in horticultural systems. - Hasler, Rachel (Cranfield University, 2023)
Organic matter addition influences soil function (respiration/ decomposition) and community structure (PLFA/ NLFA community profiles) which result in changes to the provision of soil derived ecosystem services. Additions of organic matter to gardens (e.g. composts, mulches, soil conditioners) is a widespread practice both globally and in the UK. Research on the long-term cumulative impact of annual additions to UK gardens is limited. A field trial, set-up in 2007, at the Royal Horticultural Society’s Wisley Gardens site, was used to examine the changes to soil chemical, physical and biological soil quality indicators following 12 years of different soil organic matter additions. Additions varied in carbon-to-nitrogen ratios (C/N), physical structure and macro/ micro-nutrient profiles. The amendments used in the trial included composted bark, bracken, stable manure, garden compost, spent mushroom growing compost, peat, fertiliser (rate adjusted each year to meet plant growth requirements) and controls; no organic matter addition and no plant sown, no organic matter addition and plant sown. Lab studies were designed following analyses of amendment legacy effects in field trial plots to further examine the effects of addition on microbiological indicators of soil function, health and quality. Reviewing long term chemical and physical data from the field trial highlighted significant effects of organic matter additions on soil micro- and macro-nutrients. Recommendations for garden industry were made from the findings and include the need for labelling standards for compost material packaging to reduce unwanted environmental impacts of use. Organic matter treatment to clay-loam textured soil significantly increased microbial respiration and shifted microbial community structure. The effects were distinct and dependent on composition of the organic matter applied. The horticultural sector has outlined targets for reducing the impact of garden practise on drivers of climate change. This study aligns with literature which seeks to understand common practise in order to improve economic and environmental sustainability.
Harris, Jim A. - Associate Supervisor
Keywords: soil microbiology; organic matter; microbial respiration; compost; gardens; nutrients